Activation of PKC triggers rescue of NPC1 patient specific iPSC derived glial cells from gliosis - Peter, Franziska (Orphanet J Rare Dis, 2017)
BACKGROUND: Niemann-Pick disease Type C1 (NPC1) is a rare progressive neurodegenerative disorder caused by mutations in the NPC1 gene. The pathological mechanisms, underlying NPC1 are not yet completely understood. Especially the contribution of glial cells and gliosis to the progression of NPC1, are controversially discussed. As an analysis of affected cells is unfeasible in NPC1-patients, we recently developed an in vitro model system, based on cells derived from NPC1-patient specific iPSCs. Here, we asked if this model system recapitulates gliosis, observed in non-human model systems and NPC1 patient post mortem biopsies. We determined the amount of reactive astrocytes and the regulation of the intermediate filaments GFAP and vimentin, all indicating gliosis. Furthermore, we were interested in the assembly and phosphorylation of these intermediate filaments and finally the impact of the activation of protein kinase C (PKC), which is described to ameliorate the pathogenic phenotype of NPC1-deficient fibroblasts, including hypo-phosphorylation of vimentin and cholesterol accumulation. METHODS: We analysed glial cells derived from NPC1 patient specific induced pluripotent stem cells, carrying different NPC1 mutations. The amount of reactive astrocytes was determined by means of immuncytochemical stainings and FACS-analysis. Semi-quantitative western blot was used to determine the amount of phosphorylated GFAP and vimentin. Cholesterol accumulation was analysed by Filipin staining and quantified by Amplex Red Assay. U18666A was used to induce NPC1 phenotype in unaffected cells of the control cell line. Phorbol 12-myristate 13-acetate (PMA) was used to activate PKC. RESULTS: Immunocytochemical detection of GFAP, vimentin and Ki67 revealed that NPC1 mutant glial cells undergo gliosis. We found hypo-phosphorylation of the intermediate filaments GFAP and vimentin and alterations in the assembly of these intermediate filaments in NPC1 mutant cells. The application of U18666A induced not only NPC1 phenotypical accumulation of cholesterol, but characteristics of gliosis in glial cells derived from unaffected control cells. The application of phorbol 12-myristate 13-acetate, an activator of protein kinase C resulted in a significantly reduced number of reactive astrocytes and further characteristics of gliosis in NPC1-deficient cells. Furthermore, it triggered a restoration of cholesterol amounts to level of control cells. CONCLUSION: Our data demonstrate that glial cells derived from NPC1-patient specific iPSCs undergo gliosis. The application of U18666A induced comparable characteristics in un-affected control cells, suggesting that gliosis is triggered by hampered function of NPC1 protein. The activation of protein kinase C induced an amelioration of gliosis, as well as a reduction of cholesterol amount. These results provide further support for the line of evidence that gliosis might not be only a secondary reaction to the loss of neurons, but might be a direct consequence of a reduced PKC activity due to the phenotypical cholesterol accumulation observed in NPC1. In addition, our data support the involvement of PKCs in NPC1 disease pathogenesis and suggest that PKCs may be targeted in future efforts to develop therapeutics for NPC1 disease.